Variable gearing at the ankle during walking in adults and young children: implications for foot development and evolution - Zeininger, Angel; Schmitt, Daniel; Jensen, Jody L.; Shapiro, Liza J. (Frontiers in Earth Science, 2024)
The human foot has evolved over the past seven million years from a relatively mobile, grasping appendage to a highly derived structure with a heel pad and longitudinal arch that can absorb shock at heel strike and weight-bearing yet also function as a powerful lever at toe-off. It has been proposed that the modern human foot evolved to allow our species to use "variable gearing" during walking and running. In this model, the gears of the human foot are defined relative to the ankle center of rotation as R, the distance from the ground reaction resultant vector and r, the distance from the calf muscle vector. The gear ratio defines the torque generated to propel the body or stretch the triceps surae muscles. We test the hypothesis that variable gearing is associated with modern human pedal anatomy and a heel-to-toe roll-over that allows a shift from "low gear" to "high gear" during stance. Using force plate and video analysis we examined variable gearing in adults and children engaging in adult heel strike (AHS=35), flat foot contact (FFC=39), or immature heel contact (IHC=26). Our hypothesis was partly supported. Although variable gearing was observed in IHC steps and was greater than in FFC steps, it was not as developed as in AHS steps. This may be related to anatomical and motor control differences between juvenile and adult feet, suggesting that adult anatomy, including a high arch, and neural control are critical for full use of variable gearing and that this feature would have evolved in later hominins around two million years ago with the appearance of a fully modern foot.